Assessing the association between the strength of state policies on school drug prevention and substance use disorders. (16th April 2019) - Welsh, Justine W.; Hou, Sherry Shu-Yeu; Shentu, Yujia; Lê Cook, Benjamin
Abstract: Background : Adolescent substance use has been linked to numerous adverse health, social, and educational outcomes. While there have been intensive resources placed in school-based prevention programs, the association of these policies on prevention outcomes is still unclear. State variation in policies provides an opportunity to assess the influence of school-based prevention programs. Objectives: To examine the association between the strength of state high school-based prevention programing and the prevalence of substance use disorders among adolescents ages 14–17 in the United States. Methods: National Survey on Drug Use and Health (NSDUH) data with state-level identifiers were merged with National Association of State Boards of Education (NASBE) information on school-based prevention policy strength, categorized into "required, " "recommended, " and "no policy." Unadjusted comparisons and multilevel random intercept linear regression models were estimated to assess the change in rates of substance abuse or dependence from pre- to post- policy implementation, accounting for the nesting of individuals within states. Results: Rates of alcohol and tobacco abuse/dependence were significantly lower in states that required an alcohol prevention curriculum. After covariate adjustment, rates of alcohol abuse/dependence remained significantly lower in those states. Conclusions: Reinforcing alcohol prevention messaging in school appears to have a modest association with decreased rates of adolescent alcohol use disorders, possibly in part due to a different approach to the curriculum. For other substances, policy requirements appear to be less effective in reducing the prevalence of adolescent substance use disorders, suggesting that more targeted messaging with higher-risk students may be required.